1997
DOI: 10.1116/1.589677
|View full text |Cite
|
Sign up to set email alerts
|

X-ray lithography for ⩽100 nm ground rules in complex patterns

Abstract: Complex patterns with 75-125 nm feature sizes exposed with x-ray lithography are shown. Lithographic results for 75-125 nm lines with varying pitch are compared to simulations of image formation and resist dissolution, showing good qualitative agreement. Exposure dose latitude, nested-to-isolated print bias, image shortening, linewidth change with gap, and linearity of printed linewidth versus mask linewidth are quantified for 11-22.5 m gaps. Critical dimension control error budgets for resist linewidth unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…The optimal wavelength range for X-ray lithography is dependent on resist sensitivity, mask transparency, and diffraction effects 85 and is usually regarded to be between 0.8 and 1.4 nm . At wavelengths this short, even the all-reflective optical systems used in EUV are not practical, hence proximity printing is the only alternative.…”
Section: Proximity X-raymentioning
confidence: 99%
“…The optimal wavelength range for X-ray lithography is dependent on resist sensitivity, mask transparency, and diffraction effects 85 and is usually regarded to be between 0.8 and 1.4 nm . At wavelengths this short, even the all-reflective optical systems used in EUV are not practical, hence proximity printing is the only alternative.…”
Section: Proximity X-raymentioning
confidence: 99%
“…At the NTT facility it has been demonstrated that a 55 nm lines and spaces ͑L/S͒ pattern can be printed with a mask-wafer gap of 10 m. 7 The conclusion is that these systems can be applied to the 70 nm generation, but not so easily to the 50 nm generation. 8 We now consider an illumination system to deliver exposure light in the short wavelength down to around 3 Å. ASET has recently introduced a flash exposure system, XRA-1000 by Canon, based on the aspherical mirror with a 1°grazing angle, as shown in Fig. 3.…”
Section: Proposal For a 50 Nm Pxrl Systemmentioning
confidence: 99%
“…The effects of diffraction on two-dimensional patterns are of particular interest; for example, some line end shortening has been observed, 23 although it is generally much smaller than what is observed in optical lithography today, and studies with negative resist 24 suggest that it may be insignificant with such systems. There is therefore increased interest in understanding the applicability of XRL at ground rules down to 70 nm, and studies are in progress to supplement those done previously.…”
Section: Resistmentioning
confidence: 99%